Regional integration, trade and industry in Africa - Helmut Asche (Kiel Institute for the World Economy (IfW Kiel), Poverty Reduction, Equity and Growth Network (PEGNet), 2021)
With the advent of the African Continental Free Trade Area (CFTA), regional economic integration in Africa has captured international attention and raised high hopes. In the new book "Regional Integration, Trade and Industry in Africa", the present state of economic integration on the continent is explored in the context of global trade and plans to foster industrialization. This policy brief authored by Helmut Asche summarises the book's main findings.
Keywords: 330